A Free-Choice High-Fat High-Sugar Diet Alters Day–Night Per2 Gene Expression in Reward-Related Brain Areas in Rats - Blancas-Velazquez, Aurea Susana; Unmehopa, Unga A.; Eggels, Leslie; Koekkoek, Laura; Kalsbeek, Andries; Mendoza, Jorge; la Fleur, Susanne E. (Frontiers in Endocrinology, 2018)
Under normal light-dark conditions, nocturnal rodents consume most of their food during the dark period. Diets high in fat and sugar, however, may affect the day-night feeding rhythm resulting in a higher light phase intake. In vitro and in vivo studies showed that nutrients affect clock gene expression. We therefore hypothesized that overconsuming fat and sugar will alter clock gene expression in brain structures important for feeding behavior. We determined the effects of a free-choice high-fat high-sugar (fcHFHS) diet on clock-gene expression in rat brain areas related to feeding and reward and compared them with chow-fed rats. Consuming a fcHFHS diet for 6 weeks disrupted day-night differences in Per2 mRNA expression in the nucleus accumbens (NAc) and lateral hypothalamus but not in the suprachiasmatic nucleus, habenula and ventral tegmental area. Furthermore, short term sugar drinking, but not fat feeding, up-regulates Per2 mRNA expression in the NAc. The disruptions in day-night differences in NAc Per2 gene expression were not accompanied by altered day-night differences in the mRNA expression of peptides related to food intake. We conclude that the fcHFHS diet and acute sugar drinking affect Per2 gene expression in areas involved in food reward; however, this is not sufficient to alter the day-night pattern of food intake.